Unusual Location of the Geotail Magnetopause Near Lunar Orbit: A Case Study. Issue 4 (18th April 2020) - Shang, W. S.; Tang, B. B.; Shi, Q. Q.; Tian, A. M.; Zhou, X.‐Y.; Yao, Z. H.; Degeling, A. W.; Rae, I. J.; Fu, S. Y.; Lu, J. Y.; Pu, Z. Y.; Fazakerley, A. N.; et al.
Abstract: The Earth's magnetopause is highly variable in location and shape and is modulated by solar wind conditions. On 8 March 2012, the ARTEMIS probes were located near the tail current sheet when an interplanetary shock arrived under northward interplanetary magnetic field conditions and recorded an abrupt tail compression at ∼(‐60, 0, ‐5) R E in Geocentric Solar Ecliptic coordinate in the deep magnetotail. Approximately 10 minutes later, the probes crossed the magnetopause many times within an hour after the oblique interplanetary shock passed by. The solar wind velocity vector downstream from the shock was not directed along the Sun‐Earth line but had a significant Y component. We propose that the compressed tail was pushed aside by the appreciable solar wind flow in the Y direction. Using a virtual spacecraft in a global magnetohydrodynamic (MHD) simulation, we reproduce the sequence of magnetopause crossings in the X ‐ Y plane observed by ARTEMIS under oblique shock conditions, demonstrating that the compressed magnetopause is sharply deflected at lunar distances in response to the shock and solar wind V Y effects. The results from two different global MHD simulations show that the shocked magnetotail at lunar distances is mainly controlled by the solar wind direction with a timescale of about a quarter hour, which appears to be consistent with the windsock effect. The results also provide some references for investigating interactions between the solar wind/magnetosheath and lunar nearside surface during full moon time intervals, which should not happen in general. Key Points: The large‐scale deflection of the magnetopause was observed by ARTMIES probes at lunar distance near midnight (the full moon time) The magnetopause deflection is due to the influence of the solar wind V Y ‐windsock effect This case study provides a new point of view of the interaction of the solar wind and lunar nearside surface at the full moon time